2006
DOI: 10.1007/11847250_4
|View full text |Cite
|
Sign up to set email alerts
|

Parameterizing MAX SNP Problems Above Guaranteed Values

Abstract: Abstract. We show that every problem in MAX SNP has a lower bound on the optimum solution size and that the above guarantee question with respect to that lower bound is fixed parameter tractable. We next introduce the notion of 'tight' upper and lower bounds for the optimum solution and show that the parameterized version of a variant of the above guarantee question with respect to the tight lower bound cannot be fixed parameter tractable unless P = NP, for a number of NP-optimization problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Indeed, W/2 is the average weight of satisfied equations (as the probability of each equation to be satisfied is 1/2) and, thus, is a lower bound; to see the tightness consider a system of pairs of equations of the form i∈I z i = 0, i∈I z i = 1 of weight 1. Mahajan et al [13,14] parameterized Max Lin as follows: given a Max Lin system Az = b, decide whether the total weight of satisfied equations minus W/2 is at least k ′ , where W is the total weight of all equations and k ′ is the parameter. This is equivalent to asking whether the maximum excess is at least k, where k = 2k ′ is the parameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, W/2 is the average weight of satisfied equations (as the probability of each equation to be satisfied is 1/2) and, thus, is a lower bound; to see the tightness consider a system of pairs of equations of the form i∈I z i = 0, i∈I z i = 1 of weight 1. Mahajan et al [13,14] parameterized Max Lin as follows: given a Max Lin system Az = b, decide whether the total weight of satisfied equations minus W/2 is at least k ′ , where W is the total weight of all equations and k ′ is the parameter. This is equivalent to asking whether the maximum excess is at least k, where k = 2k ′ is the parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Mahajan et al [13,14] raised the question of determining the parameterized complexity of Max Lin AA. It is not hard to see (we explain it in detail in Section 2) that we may assume that no two equations in Az = b have the same left-hand side and n = rankA.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of parameterized complexity, since a minimum vertex cover of an n-vertex graph with perfect matching contains at least n/2 vertices, it seems more reasonable to parameterize the problem by studying whether such a graph has a vertex cover of size bounded by n/2+k, where k is the parameter [18][19][20]. This way of problem parameterization has been named "parameterizing above or below guaranteed values" in [20], which has received increasing attention recently.…”
Section: Introductionmentioning
confidence: 99%
“…For more background on kernelization we refer to the recent surveys on kernelization given by Guo and Niedermeier [23] as well as by Bodlaender [4]. In an earlier paper, Mahajan et al [31] studied MAX SNP problems and observe that kernelizations follow from the fact that NP-hard problems in MAX SNP have guaranteed lower bounds for the optimum value, motivating them to study these problems parameterized above such lower bounds. Cai and Huang [9] showed that all problems in MAX SNP admit fixed-parameter approximation schemes.…”
Section: Introductionmentioning
confidence: 99%